ENVIRONMENTAL EDUCATIONIN THE SYSTEM OF GLOBAL AND ADDITIONAL EDUCATION - M. R. Arpentieva; G. K. Kassymova; S. V. Lavrinenko; Z. I. Tyumaseva; G. V. Valeeva; O. B. Kenzhaliyev; M. B. Triyono; O. N. Duvalina; A. V. Kosov (Scientific Journal of Pedagogy and Economics, 2019)
The purpose of the study is to analyze the significance of the role of global and additional education in the formation of common cultural, common human competencies of future generations. A comparative analysis of the characteristics of the content and forms of global and additional education in Russia and in the world makes it possible to assess the prospects of these types of education from the point of view of environmental education (education and upbringing) as an important component of human competences. Environmental education plays a strategic role in the system of global and additional education. Environmental education - the leading competence of students and trainees in relation to the world around them and themselves: the ability to live in harmony with nature and culture, with themselves and with society - leading orienteer global education. These benchmarks are also guidelines for students' self-development. The article deals with the pedagogical support of person's self-development in the context of solving the problem of self-development of the individual, acting as one of the leaders in the context of the globalization of modern education. The possibilities (pedagogical resources) of the additional education of the person in the self-development of the individual and the realization of pedagogical ideas of Russian space scientists are shown, the appeal to which acquires particular relevance in the light of the globalization of education.